PENGEMBANGAN E-MODUL BERBASIS SMARTPHONE PADA MATERI BANK DAN SISTEM PEMBAYARAN UNTUK PESERTA DIDIK KELAS X DI SMA NEGERI 1 BASO KABUPATEN AGAM SUMATERA BARAT - Viona Amelia; Caska Caska; Mifta Rizka (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This development research was conducted because of the students' understanding of the material was still not stable and they tended to be bored when following the learning process. The aim of this research is to add learning resources to make it easier for students to understand the material and make students more interested in participating in learning through smartphone-based e-modules. This development research uses a development model (R&D) with the ADDIE model. The e-module development before being tested was validated by material experts and e-module experts, with the research subjects was students of class X SMA Negeri 1 Baso. The results of the validation of materials and e-modules obtained an overall average score of 4.67 and 4.93 these values were included in the very decent. the results of a limited trial that was tested on teachers and students obtained an overall percentage of 97.3% of the teacher's response and 85.15% of the student's response, the value was included in the very effective.Keywords: E-module, development, smartphone, bank, payment systems